1999
DOI: 10.1006/jmaa.1999.6331
|View full text |Cite
|
Sign up to set email alerts
|

All Solutions of Standard Symmetric Linear Partial Differential Equations Have Classical Lie Symmetry

Abstract: It is proven that every solution of any linear partial differential equation with an independent-variable-deforming classical Lie point symmetry is invariant under some classical Lie point symmetry. This is true for any number of independent variables and for equations of any order higher than one. Although this result makes use of the infinite-dimensional component of the Lie symmetry algebra due to linear superposition, it is shown that new similarity solutions, previously thought not to be classical, can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…Through (b 3 ) and (b 4 ), we can obtain 6 ) into other equations we can obtain the determining equations for the nonclassical symmetries of the Boussinesq equation, and it reads as follows:…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Through (b 3 ) and (b 4 ), we can obtain 6 ) into other equations we can obtain the determining equations for the nonclassical symmetries of the Boussinesq equation, and it reads as follows:…”
Section: Examplesmentioning
confidence: 99%
“…Recently in Ref. [6] Broadbridge and Arrigo have shown that all solutions of standard symmetric linear partial differential equations have classical Lie symmetry. In addition to the nonclassical method, the determining equations are usually highly nonlinear unlike the determining equations for the classical method which are linear (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In what follows, we omit the cases where (11) are linear or linearizable via a point transformation, as it is known that all solutions of linear PDEs can be obtained via classical Lie symmetries [30]. Each equation will be considered separately.…”
Section: Nonclassical Symmetriesmentioning
confidence: 99%
“…(2.27). Thus we put 45) and must prove that the coefficients B a are finite and depend on σ in the proper way (i.e. B a = B a σ n+1−a , where B a is finite and does not depend on σ).…”
Section: Theorem 24 the Expressionmentioning
confidence: 99%